Teacher Experience of Ethnoscience: Local Wisdom in Independent Curriculum Implementation - Yeni Widiyawati; Dwi Septiana Sari; Ina Sholihah Widiati (Jurnal Penelitian Pendidikan IPA, 2023)
It is expected of teachers to be able to design and manage the instruction effectively. Learning will become meaningful if local wisdom and indigenous knowledge are presented in the science classes in accordance with the current curriculum through ethnoscience. This research was to explore the science teacher experiences about ethnoscience implementation in independent curriculum framework at junior high school level. This research uses a qualitative method known as phenomenology to explore participants' experiences. Four science teachers were involved as participants in this research through in-depth interviews and questionnaires. Science teacher experiences in designing and manage ethnoscience learning according to the independent curriculum is the primary data which is analysed with ATLAS.ti software. The connection between four themes, i.e. differentiated instruction, Pancasila student profile, local wisdom and contextual teaching and learning is the main finding in this research. Science teachers have carried out these key themes not only in the preparation but also in the process in order of gaining mastery earning.